Clinical application of the sentinel lymph node technique in early ovarian cancer: a pilot study. Issue 2 (21st December 2018) - Lago, V; Bello, P; Montero, B; Matute, L; Padilla-Iserte, P; Lopez, S; Agudelo, M; Domingo, S
Abstract : Introduction: There is limited evidence favoring the use of the sentinel lymph node technique in ovarian cancer, and no standardized approach has been studied. The objective of the present pilot study is to determine the feasibility of the sentinel lymph node technique by applying a clinical algorithm. Methods: Patients with confirmed ovarian cancer were included. 99mTc and indocyanine green were injected into the ovarian and infundubulo-pelvic ligament stump. A gamma probe and near-infrared fluorescence imaging were used for sentinel lymph node detection. Results: The sentinel lymph node technique was performed in nine patients with a detection rate in the pelvic and/or para-aortic region of 100%. The tracer distribution rates of sentinel lymph nodes in the pelvic and para-aortic regions were 87.5% and 70%, respectively. Conclusion: The detection of sentinel lymph nodes in early-stage ovarian cancer appears to be achievable. Based on these results, a clinical trial entitled SENTOV (SENtinel lymph node Technique in OVarian cancer) will be performed.